The safety and efficacy of botulinum toxin for management of scars: A systematic review with meta-analysis and trial sequential analysis. (August 2019) - Wang, Di; Qu, Jiaorong; Jiang, Haiyue; Jiang, Yu
Abstract: Scars can have a dramatic impact on patients' physical appearance and function. Injection of botulinum toxin has been used to prevent scar formation at the site of injury and to remodel scars that have already formed. The purpose of this review is to assess the safety and efficacy of botulinum toxin for scar management compared to placebo or no treatment. MEDLINE, EMBASE, Web of Science, the Cochrane Central Register of Controlled Trials and PubMed Central were searched. Nine randomized controlled trials comparing injections of botulinum toxin versus placebo or no treatment for individuals of any age with scars were included and were assessed by two independent review authors. Cochrane risk of bias was used to assess trial quality, sensitivity analyses was conducted and trial sequential analysis was employed to assess the risk of random error. Mean difference (MD), standardized mean difference (SMD) and 95% CI were calculated for continuous outcomes. Risk ratios (RR) and corresponding 95% confidence intervals (CI) were calculated for all dichotomous outcomes. The MD for the Vancouver scar scale (VSS) was −0.87 (95%CI, −1.73 to −0.02), and for the visual analogue scale (VAS) was 1.30 (95%CI, 1.05 to 1.54). The SMD for scar width was −1.05 (95%CI, −1.29 to −0.81). The safety of botulinum toxin therapy was evaluated by calculating adverse events and complications (RR 0.36; 95%CI, 0.09 to 1.45). Evidence from this study has documented the clinical benefits of botulinum toxin versus placebo or no treatment in the prevention and remodeling of scars. Injection of botulinum toxin is both safe and effective. Future studies should focus on the different doses needed and differences in effects between pre-surgical and post-surgical injection periods. Highlights: Management of scars can be done using both surgical and non-surgical methods. Botulinum toxin is the treatment of choice for scars. This review was conducted to update low-quality research data of scar management from a previously reported article. PRISMA guidelines were followed in conducting and reporting this review. Nine RCTs were included and evaluation indicates that injection of botulinum toxin is both safe and effective.